(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Introduction: Soft tissue defects around the ankle and posterior heel need stable flap coverage for proper healing and satisfactory recovery of function. Constant and reliable vascular supply of reverse sural island flap (RSIF) have made it a popular choice for reconstruction of these defects. In this study, the outcome of RSIF with few modifications in the pedicle area were discussed. Methods: This prospective study was carried out in National Institute of Traumatology and Orthopedic Rehabilitation (NITOR), Dhaka duing April 2019 to June 2020. Total 31 patients with soft tissue defect around ankle and posterior heel were reconstructed with reverse sural artery island flap. The soft-tissue defects were located, infront of ankle in 3 cases, over lateral malleolus in 7 cases, over medial malleolus in 5 cases, over tendoachilles in 12 cases, involving two or more areas of posterior heel, tendoachilles and lateral malleolus in 4 cases. Average Flap length and width were 9.67(+1.60) cm & 6.38(+0.76) cm respectively. Pedicle area of flap was modified by including a 2 cm skin extension in the middle along with additional adipofascial tissue on both sides to improve venous return. Pedicle length to width ratio was maximum of 3:1. Average length of pedicle was 7.2 + 1.7 cm. Results: All flaps except three survived completely without any complications. One patient (3%) had partial necrosis and another one (3%) had marginal necrosis of flap due to venous congestion. Epidermolysis was observed in 3% cases. Conclusions: The distally based superficial sural artery island flap is a versatile, reliable procedure useful in reconstruction of the lower extremity. Modifying the design of pedicle area increases safety by reducing venous congestion which ultimately leads to increase flap survivability. J Bangladesh Coll Phys Surg 2024; 42: 126-132